Optimization of the Operation and Frequency Control of Electromagnetic Vibratory Feeders - Sinik, Vladimir; Despotovic, Zeljko; Palinkas, Ivan (Elektronika ir Elektrotechnika, 2016)
A realized frequency and amplitude controlled power converter for driving electromagnetic vibratory feeders is presented. By using a microcontroller-based control system designed for the converter, it was possible to accomplish continuous variation of the frequency and amplitude of vibrations, perform search of the resonant frequency of the mechanical vibratory system, and maintain the system in the state of resonance. Operation in the resonance mode is convenient since consumption of the system is kept at minimum. Finally, the corresponding experimental results are presented. DOI: http://dx.doi.org/10.5755/j01.eee.22.1.14095